EVALUATION OF THE EFFICIENCY OF EXECUTIVE AUTHORITIES AND CIVIL SERVANTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article focuses on the forms and methods of evaluating the effectiveness of executive authorities and civil servants. The article analyzes the work of scientists who conduct research in the field. The article also discusses the relationship between the concepts of "New Government", "Quality Public Administration", "New Public Services" and the performance of government agencies and employees, as well as some suggestions based on the results of the study.